2013
DOI: 10.1017/s0922156513000095
|View full text |Cite
|
Sign up to set email alerts
|

Diplomatic Asylum and the Assange Case

Abstract: This article traces the place and development of diplomatic asylum in international law in close connection with the more specific questions raised by the case of Julian Assange, who was granted asylum in the Ecuador embassy in London on 16 August 2012. After discussing the historical rise and decline of diplomatic asylum, the article reviews the current status of diplomatic asylum in international law and its implications for the triangular legal relationship between the United Kingdom, Ecuador, and Mr Assang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…48 People arriving there without authorization by boat, are not entitled to an entry visa for mainland Australia, and Australia's domestic migration law does not apply-which means that no recourse to the judiciary against expulsion or other acts is possible. The 45 See for elaborate descriptions and discussions of the Guantanamo Bay regime, Legomsky 2006 andDen Heijer 2011, at 277-279 with further references. 46 corollary of the scheme was the intent to move these asylum seekers to a third country where their applications would be processed and from where they, eventually, could be resettled to enjoy asylum in Australia or elsewhere.…”
Section: Australia's Excised Territoriesmentioning
confidence: 99%
“…48 People arriving there without authorization by boat, are not entitled to an entry visa for mainland Australia, and Australia's domestic migration law does not apply-which means that no recourse to the judiciary against expulsion or other acts is possible. The 45 See for elaborate descriptions and discussions of the Guantanamo Bay regime, Legomsky 2006 andDen Heijer 2011, at 277-279 with further references. 46 corollary of the scheme was the intent to move these asylum seekers to a third country where their applications would be processed and from where they, eventually, could be resettled to enjoy asylum in Australia or elsewhere.…”
Section: Australia's Excised Territoriesmentioning
confidence: 99%
“…In fact, our FEA calculations as well as calculations by other group members showed that the coarse approach is very often the most susceptible part of the mechanical loop. 14,15 The coarse approach mechanisms can be divided into two groups: those containing piezo elements (either tubes, or stacks), and those consisting of an electrical motor and screws and/or flexible hinges. If one looks at material properties of different piezo materials and compares them with the material properties of, e.g., stainless steel, it is obvious that a system containing no piezo elements in the mechanical loop would be the stiffest one.…”
Section: Coarse Approach Mechanismmentioning
confidence: 99%
“…In fact, in the calculations a constant, frequencyindependent loss factor has been used to account for material damping. 14,15,33 It is known that this is a rather rough approximation underestimating damping especially for higher frequencies. Therefore, the calculated results can be viewed as the worst case scenario in terms of the amplitude values at resonances.…”
Section: B Prototype Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…Por el momento, sobre tales posibilidades e hipotéticas alternativas, sus numerosos detractores han sostenido que, siendo una suerte de uso internacional regional, su extensión solo puede constituir un abuso del privilegio de la inmunidad de los recintos de las misiones diplomáticas y consulares (Sosnowoski, 1985). Son ilustrativas las opiniones de dos autores que coinciden sobre un extremo convergente: «ningún Estado puede verse obligado a soportar una invocación de esta práctica de asilo diplomático al no tener como base ni el derecho convencional ni consuetudinario» (Mangas, 2008) (Den Heijer, 2013). Ahora bien, aun siendo escasas las voces favorables a la necesidad de «rescatar» del olvido una institución «fantasmagórica» y ciertamente singular en sus términos jurídicos para Europa, bajo mi punto de vista, plantearse hipotéticamente su encaje a nivel europeo en términos de oportunidad, resulta apremiante ante la actual coyuntura de gestión de los contextos migratorios globales en el viejo continente.…”
Section: Introductionunclassified